Improved meet-in-the-middle attack on ARIA cipher - Man-man LI; Shao-zhen CHEN (Tongxin xuebao)
A study on the structure of ARIA cipher is presented. A new 4-round distinguishing property for the meet-in-the-middle attack on ARIA cipher is presented by making use of the multiset and the truncated differential char-acteristic. The new distinguishing property improves the meet-in-the-middle attack on 7 rounds of ARIA-192 cipher ef-fectively by reducing the 30 parameters to 16. The new attack requires a precomputation complexity of 2135.3and a time complexity of about 2123.